New-Onset Diabetes after Transplantation (NODAT) in Renal Transplant Recipients, A Retrospective Single Centre Study - Adil Manzoor, Muhammad Bilal Basit, Anam Tanveer, Sheharbano Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: New onset diabetes after transplant (NODAT) is a known post-transplant complication contributing to morbidity and mortality. This study was aimed to find out the frequency of NODAT in kidney disease patients after one year. Methods and subjects: The study was conducted retrospectively on 275 Asian patients who underwent kidney transplant. The demographic and clinical data was evaluated at the time, as well as 3, 6, and 12 months after kidney transplant. The etiology of end-stage renal disease (ESRD) or comorbidities was also documented. Every patient received a combination of Tacrolimus (Tac), Mycophenolate Mofetil (MMF), and Prednisone (Pred) as post-transplant immunosuppression. Patients who developed NODAT were compared with those who did not. RESULTS: One year after the transplantation, the incidence of NODAT was 4.3 percent. Patients diagnosed with NODAT were older (p = 0.001) and had renal failure owing to Chronic glomerulonephritis with hypertension (p = 0.001), according to the results of the univariate analysis. The NODAT group had significantly greater rates of high blood pressure after transplantation (p = 0.01), heart failure (p = 0.02), and dyslipidemia (p = 0.001) than the other groups. Through the use of logistic regression, it was shown that high blood pressure after transplant, and dyslipidemia are all independently linked with NODAT. Conclusion: Asian patients who had high blood pressure and dyslipidemia had a higher incidence of NODAT compared to those who did not have.